The influence of nitrogen oxides on the activation of bromide and chloride in salt aerosol - Bleicher, S.; Buxmann, Joëlle; Sander, R.; Riedel, Theran P.; Thornton, Joel A.; Platt, Ulrich; Zetzsch, Cornelius (Atmospheric chemistry and physics. Discussions, 2014)
Abstract. Experiments on salt aerosol with different salt contents were performed in a Teflon chamber under tropospheric light conditions with various initial contents of nitrogen oxides (NOx = NO + NO2). A strong activation of halogens was found at high NOx mixing ratios, even in samples with lower bromide contents such as road salts. The ozone depletion by reactive halogen species released from the aerosol, was found to be a function of the initial NOx mixing ratio. Besides bromine, large amounts of chlorine have been released in our smog chamber. Time profiles of the halogen species Cl2, Br2, ClNO2, BrNO2 and BrO, ClO, OClO and Cl atoms were simultaneously measured by various techniques (chemical ionization mass spectrometry, differential optical absorption spectrometry coupled with a multi-reflection cell and gas chromatography of hydrocarbon tracers for Cl and OH, employing cryogenic preconcentration and flame ionization detection). Measurements are compared to calculations by the CAABA/MECCA 0-D box model, which was adapted to the chamber conditions and took the aerosol liquid water content and composition into account. The model results agree reasonably with the observations and provide important information about the prerequisites for halogen release, such as the time profiles of the aerosol bromide and chloride contents as well as the aerosol pH.